Let's steal the moon : Jewish tales, ancient and recent - Serwer-Bernstein, Blanche, author; Hyman, Trina Schart (Boston : Little Brown & Co., 1970)
Eleven traditional tales from Jewish folklore of the Middle East and Europe.
Keywords: Jewish folk literature; Legends, Jewish; Jews -- Folklore